The magic bullet as cancer therapeutic—has nanotechnology failed to find its mark?. (18th September 2020) - Xiong, Gordon Minru; Venkatraman, Kailash; Venkatraman, Subbu
Abstract: Ever since the term 'Magic Bullet' was coined by Nobel laureate Paul Ehrlich to denote selective activity of a therapeutic medicine against a particular target tissue or organism, researchers have been attempting to develop the concept, with the major part of the work directed towards cancer targets. In this review, we define four major technologies that embody the Magic Bullet concept, and discuss the status of the therapeutic in each case. The reasons for relative success and failure of the four technologies are assessed based on the clinical outcomes. There have been failures of ancillary concepts (to enable selectivity) such as the enhanced permeation and retention effect, which will be discussed in context. The outlook is hopeful, with the advent of immunotherapies, that the idealized Magic Bullet will see the light of day in the near future.